Fenomena program Ridwan Hasan dalam pembelajaran MNR pada program “Belajar di Rumah” siswa sekolah dasar - Yuni Setyowati; Sandra Bayu Kurniawan; Peduk Rintayati (Didaktika Dwija Indria, 2021)
The purpose of this research is to describe the MNR method in mathematics learning delivered by Ridwan Hasan in the TVRI program "Belajar di Rumah". This research used descriptive qualitative method with phenomenological approach. The informants in this research were students in V grade of Elementary School in 2020/2021 academic year at Pringkuku District, Pacitan city. The sampling technique used was a purposive sampling. The data collection technique was done by observation, interviews, and analysis documents. The data validity test used source triangulation and time triangulation. Data analysis used Miles and Huberman's model. The results of this study indicate that MNR method is quite helpful for students in understanding Mathematics during online learning. The MNR method steps that Pak Ridwan presented are in accordance with the MNR syntax theory. The display of the segment "Gemar Matematika Bersama Pak Ridwan" which uses animations and interactive images makes students interested in Mathematics learning. A unique variation in learning is the use of traditional clothing that changes every day which attracts the curiosity of students. Apart from functioning as variations in learning, the use of traditional clothing is also beneficial for students to gain new knowledge and insights about customs in IndonesiaKeywords: Mathematics, Online learning, MNR method, Elementary School.